Short-term outcomes of deeper intubation technique of ileus tube for different types of acute intestinal obstruction patients: A retrospective multicenter study - Tan, Yanlu; Yin, Fangxu; Lu, Zhihua; Huang, Peng; Zhang, Chengcai; Sun, Jiuzheng; Wang, Song; Dong, Zhensheng (Frontiers in Oncology, 2022)
Background Our previous research reported a novel deeper intubation technique (DIT) of the ileus tube for acute bowel obstruction patients. The present study was designed to evaluate the effect of this novel technique on the clinical outcomes of patients with obstruction using a large cohort. Methods The detailed clinical data were analyzed retrospectively from 496 obstruction patients who underwent intubation technique from 2014 to 2019 in five hospitals. The patients were divided into either the DIT group or the traditional intubation technique (TIT) group. The groups were matched in a 1:1 ratio using propensity scores, and the primary outcome was the short-term clinical outcomes for patients. Results The baseline characteristics were similar between the DIT group and the TIT group after matching. Compared with the TIT group, the DIT group had a significantly deeper intubation depth, with shorter hospital days, shorter time to first flatus and defecation, lower pain score, increased drainage volume, and lower emergency surgery rate. Importantly, the inflammatory factors such as white blood cell, C-reactive protein, and procalcitonin levels were significantly lower in the DIT group. In addition, the DIT treatment was significantly useful for adhesive obstruction patients. Conclusion The DIT procedure led to better short-term clinical outcomes compared with the TIT procedure, indicating that DIT is a safe and feasible technique for the treatment of intestinal obstruction that is worthy of further popularization and clinical application.